The production of h.perforatum oil incorporated antibacterial thermoplastic polyurethane (TPU) nanofibre mat - Keskinkaya, Rüya (Graduate School, 2022)
In the content of this thesis, a novel wound dressing was engineered by combining thermoplastic polyurethane (TPU), fish skin gelatin (FSG) and H.Perforatum Oil (H.P.Oil) via the emulsion electrospinning technique. Scanning Electron Microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), Thermogravimetric Analysis (TGA), water contact angle (WCA), water vapour transmission rates (WVTRs) and the fluding handling capacities and solution immersed pH measurements were performed on the obtained TPU mats. In addition incorporation of a bioactive component, like H.P.Oil, into the nanofibre scaffolds, defectless and thin fibres were obtained with roughly 400-500 nm of average fibre diameters, which are suitable to mimic the native Extracellular Matrix (ECM) with these diameters. FTIR results confirmed the interaction between the components and the presence of H.P.Oil within nanofibres. According to WCA measurement, H.P.Oil addition was predicted to contribute to protein adsorption and promote wound healing thanks to increasing surface hydrophobicity on the dressing. The absorbing the exudate and transmitting water vapour performance of the TPU nanofiber mats' were as much as literature data of Versiva® XC® used for moderate to high exudating wounds. H.P.Oil addition decreased the solution immersed pH of the mats to slightly acidic levels, which is optimum for proteinase and cellular activities. The inclusion of H.P.Oil into TPU nanofibre scaffolds promoted antibacterial efficiency against both S.Aeurus and E.Coli bacteria. In conclusion, the produced H.P.Oil encapsulated TPU nanofibre mats indicate a promising dressing candidate for wound dressing application.
Sarı kantaron yağı dahil edilmiş antibakteriyel termoplastik poliüretan (TPU) nanofiber matların üretimi
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2022
Keywords: antibacterial activity; antibakteriyel aktivite; electrospinning method; elektroeğirme yöntemi; gelatin; jelatin; nanotechnology; nanoteknoloji; polymer materials; polimer malzemeler; thermoplastic materials; termoplastik malzemeler